PRENATAL YOGA MENGURANGI KECEMASAN IBU HAMIL PRIMI GRAVIDA DALAM MENGHADAPI PERSALINAN - Islah Wahyuni; Desi Nindya Kirana; Susani Hayati (LPPM Universitas Abdurrab, 2023)
The experience of vaginal delivery will certainly vary for some pregnant women, especially primi gravida who have never been at all and get experience from stories of friends, relatives, books and information from social media. The existence of anxiety and fear of not being able to give birth normally can have an impact on the mental readiness of the mother in facing the labor process. The aims is to identified influence of prenatal yoga to reduce anxiety in facing of labor. The design in this study is a prospective study. The sample in this study were primi gravida pregnant women TM III, namely 12 respondents at the Independent Midwife Practice. Providing Prenatal Yoga Exercise 4 times for 1 hour, the anxiety status of respondents using the Perinatal Anxietas Screening Scale (PASS). Bivariate analysis was tested with Paired T-test. The results showed that prenatal yoga can reduce the anxiety of Primi Gravida mothers in facing labor with a value of p=0.000 (p<0.005). There is a low relationship between panic and anxiety in the facing of labor. Pregnant women are advised to do prenatal yoga regularly during their pregnancy.